Numerical analysis of hybrid electromagnetic coil designs for efficient gradient field generation in magnetic particle imaging - Shahriar Mostufa; Ebrahim Azizi; Bahareh Rezaei; Changzhi Li; Jenifer Gómez-Pastora; Rui He; Kai Wu (AIP Advances)
Magnetic particle imaging (MPI) is an emerging tomographic imaging modality that has shown great potential for cell tracking, tumor imaging, gut bleeding, etc. As MPI moves towards clinical applications, one challenge faced by this technology is the increasing power consumption for field generation as the bore size increases. Joining the efforts in transitioning MPI to clinical applications, especially for human-sized MPI. Herein, using COMSOL Multiphysics, we numerically studied three coil designs for generating high gradient fields with high field uniformity at lower power consumption. Specifically, the Maxwell electromagnetic (EM) coils, the hybrid EM coils with an NdFeB magnet core, and the hybrid EM coils with an NdFeB magnet core designed as a magnetic flux concentrator (MFC). We first compared the efficiency of these three coil designs in generating gradient fields by evaluating the maximum gradient field strength and field uniformity. With the same current applied to these coils, the hybrid EM coils with a NdFeB MFC core show the best gradient field profiles, achieving a maximum gradient field strength of 5 T/m. The current supplied to these EM coils and the coil winding layers are varied to study their effects on the gradient field profiles. Additionally, the geometrical parameter of the MFC structure is optimized, and we have achieved a maximum gradient field strength of 5 T/m over a 14.3 cm space, with a tolerance of 98%.